Relaxed skin tension lines and epidermal inclusion cyst: case report - Munjal, Manish; Kaur, Japneet; Talwar, Gopika; Kaur, Amanjot; Munjal, Shubham; Garg, Abhinav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Facial cosmesis is the primary concern, whatsoever maybe the lesion, benign or malignant. The subject wishes that the facial features be retained and the surgeon, that his handiwork is appreciated. Utilising the relaxed skin tension lines and the wrinkle creases one, can usually achieve an obnoxious scar free face. Such an intervention was undertaken in an individual with an indwelling inclusion cyst in the naso-maxillary groove.